2021
DOI: 10.1590/2177-9465-ean-2020-0320
|View full text |Cite
|
Sign up to set email alerts
|

HIV/AIDS em região de tríplice fronteira: subsídios para reflexões sobre políticas públicas

Abstract: RESUMO Objetivo analisar a tendência dos casos de HIV/Aids por sexo e faixa etária nas cidades gêmeas de Mato Grosso do Sul. Método estudo ecológico de série histórica. Foram utilizadas as fichas de notificação de HIV/Aids, do período de 2009 a 2018, disponibilizadas pela Secretaria de Estado de Saúde e analisadas segundo estatística descritiva, regressão polinomial e geoespacialização dos casos. Resultados foram registradas 734 notificações, sendo 57,9% em homens, e com maior incidência no biênio 2017-2018… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
3
0
2

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 29 publications
(37 reference statements)
0
3
0
2
Order By: Relevance
“…Uma possível explicação para este fato pode estar ligada às suas características geográficas, sendo um município situado próximo à fronteira com a Bolívia. Áreas de fronteira geralmente apresentam maior vulnerabilidade à infecção por HIV entre populações imigrantes em comparação a população local, devido a dificuldades de acesso aos serviços de saúde, xenofobia ou falta de conhecimento sobre direitos à saúde ( 31 ).…”
Section: Discussionunclassified
“…Uma possível explicação para este fato pode estar ligada às suas características geográficas, sendo um município situado próximo à fronteira com a Bolívia. Áreas de fronteira geralmente apresentam maior vulnerabilidade à infecção por HIV entre populações imigrantes em comparação a população local, devido a dificuldades de acesso aos serviços de saúde, xenofobia ou falta de conhecimento sobre direitos à saúde ( 31 ).…”
Section: Discussionunclassified
“…Furthermore, the latter are not highlighted in virus prevention policies or actions, which makes them vulnerable to infection. [11][12][13] Not performing PE corresponded to 67% of the total individuals in the sample. A study in the United States on physical activity in PLHIV showed that the majority of patients (68%) had low adherence.…”
Section: Discussionmentioning
confidence: 99%
“…Key populations in relation to HIV -homosexuals and other men who have sex with men (MSM), sex workers and their clients, transgender individuals, and people who use injectable drugs -still lack social support when facing serophobic situations 5 . This justifies the study, especially in terms of the imagery and media construction surrounding the phenomenon of serophobia, with a focus on health promotion and prevention actions, legal protection, assertive communication, guaranteeing social rights, and comprehensive healthcare practices 6 .…”
Section: Introductionmentioning
confidence: 92%